Functions of interdisciplinary integration in the development of education as a system - T E Titovets (Peoples' Friendship University of Russia (RUDN University), 2010)
The article reveals three major groups of regularities according to which education develops. It defines the message of interdisciplinary integration in their realization and outlines its main and applied functions in education development.